The circadian clock has transient plasticity of period and is required for timing of nocturnal processes in Arabidopsis - Dodd, Antony N; Dalchau, Neil; Gardner, Michael J; Baek, Seong Jin; Webb, Alex AR (New Phytologist, 2013)
A circadian rhythm matched to the phase and period of the day–night cycle has measurable benefits for land plants. We assessed the contribution of circadian period to the phasing of cellular events with the light : dark cycle. We also investigated the plasticity of circadian period within the Arabidopsis circadian oscillator. We monitored the circadian oscillator in wild-type and circadian period mutants under light : dark cycles of varying total duration. We also investigated changes in oscillator dynamics during and after the transition from light : dark cycles to free running conditions. Under light : dark cycles, dawn and dusk were anticipated differently when the circadian period was not resonant with the environmental period (‘T cycle’). Entrainment to T cycles differing from the free-running period caused a short-term alteration in oscillator period. The transient plasticity of period was described by existing mathematical models of the Arabidopsis circadian network. We conclude that a circadian period resonant with the period of the environment is particularly important for anticipation of dawn and the timing of nocturnal events; and there is short-term and transient plasticity of period of the Arabidopsis circadian network.